Strong Correlation between Molecular Configurations and ChargeTransfer Processes Probed at the Single-Molecule Level by SurfaceEnhanced Raman Scattering - Cortés, Emiliano (2013)
Single-molecule (SM) electrochemistry studied by surface-enhanced Raman scattering (SERS) with high spectral resolution reveals a picture in which the frequency of Raman modes is correlated with the electrochemical process through the interaction with the surface. Previously unexplored phenomena can be revealed by the synergy of electrochemistry and SM-SERS, which explores in this case subtler spectroscopic aspects (like the frequency of a vibration within the inhomogeneous broadening of a many-molecules Raman peak) to gain the information. We demonstrate, among other things, that the interaction with the surface is correlated both with the molecule vibrational frequencies and with the ability of single molecules to be reduced/oxidized at different potentials along the electrochemical cycle. Qualitative models of the interaction of molecules with surfaces are also touched upon.